2022
DOI: 10.12659/msm.939065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibacterial Activity, Cytotoxicity, and Fluoride Release of Glass Ionomer Restorative Dental Cements in Dentistry

Abstract: Background:This study aimed to compare the antibacterial activity, cytotoxicity, and fluoride release of 4 different glass ionomer cements (GIC). Material/Methods:A total of 200 samples were prepared: Riva Silver, a silver-reinforced GIC; Equia Forte HT, a glass hybrid GIC; ChemFil Rock, a zinc-added GIC; and Ketac™ Molar Easymix. Using the agar diffusion test for antibacterial activity, 30 samples from each group were analyzed for Streptococcus mutans, Lactobacillus acidophilus, and Actinomyces naeslundii. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Silver-reinforced GIC includes the incorporation of silver particles into the glass ionomer matrix. [ 8 , 9 ] Result of resent In-vitro study showed a significantly higher CS and DTS of the S-GIC over the C-GIC underscores a critical advancement in dental material technology. The addition of silver particles is intended to increase the compressive and tensile strength of the cement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver-reinforced GIC includes the incorporation of silver particles into the glass ionomer matrix. [ 8 , 9 ] Result of resent In-vitro study showed a significantly higher CS and DTS of the S-GIC over the C-GIC underscores a critical advancement in dental material technology. The addition of silver particles is intended to increase the compressive and tensile strength of the cement.…”
Section: Discussionmentioning
confidence: 99%
“…Upon the introduction of novel materials, it is imperative to possess a comprehensive understanding of their physical and mechanical properties, as well as to conduct clinical evaluations, prior to their adoption in clinical settings. [ 9 ] The compressive strength test and the diametral tensile strength test emerge as the predominant methodologies for evaluating the mechanical characteristics of the newly introduced cements. Therefore, it is of interest to conduct a comparative analysis and evaluation of the CS and DTS between a traditional Glass Ionomer Cement and a Silver-reinforced GIC.…”
Section: Introductionmentioning
confidence: 99%
“…Resin-modified glass ionomer cements (RMGICs) were developed to improve the physical and mechanical properties of GICs [16]. These materials undergo a dual-setting reaction, the typical acid-base reaction of GICs, and photopolymerization [17].…”
Section: Introductionmentioning
confidence: 99%
“…Resin-modified glass ionomer cements (RMGICs) were developed to improve the physical and mechanical properties of GICs [ 21 ]. The most common resin monomer is 2-hydroxyethyl methacrylate (HEMA), to which a photoinitiator, such as camphoroquinone, is added to allow a light-mediated setting.…”
Section: Introductionmentioning
confidence: 99%